Dual adaptation for biodiversity and people: Nexus in ecological protection using a case study of the Qilian Mountains in China. (November 2022) - Yang, Zhenshan; Zhang, Yilin; Su, Huimin; Wang, Jieyong
Highlights: Ecosystem-based management requires both overall and internal knowledge of the ecoregion. A dual approach to combine biodiversity and human value in ecosystem management. The Qilian Mountain Protected Area in China was used as a case study area. Ecosystem-based adaptations for biodiversity (EbA-BI) and humans (EbA-HI) compared. These are sensitive metrics that will help achieve optimal EBM. Abstract: Ecosystem-based management (EBM) has attracted wide attention in climate change adaptation strategy. However, EBM requires the realization of co-benefits of biodiversity and human wellbeing improvement. Furthermore, overall and internal knowledge of the ecoregion of interest is essential. With this knowledge, EBM can be integrated better into the spatial planning process. The present study proposes a dual service strategy for ecosystem-based adaptation (EbA): the ecosystem-based adaptation for human index (EbA-HI) and the ecosystem-based adaptation for biodiversity index (EbA-BI), which are examined at finer spatial scales. The Qilian Mountain protected area was used as an example to investigate the spatiotemporal characteristics of the two indices. Panel quantile regression was used to identify factors influencing the spatial distribution variations. Both EbA-HI and EbA-BI increased by 1.87% and 0.84%, respectively, from 2003 to 2019 in the Qilian Mountain Protected Area. Nevertheless, variations in the values of these indices, as well as their factors, were evident in different areas. Higher air temperatures significantly facilitated the increase in both EbA-HI and EbA-BI. A higher degree of land use positively affected EbA-HI but negatively impacted EbA-BI. Our findings illustrate the complexity associated with EbA and elucidate the need for in-depth theoretical thinking and practical adaptation measures for efficient ecosystem management, which will help to sustain and improve both biodiversity and human well-being.